Corporate social responsibility corporate innovation: A cross‐country study of developing countries. (4th January 2021) - Ullah, Subhan; Sun, Di
Abstract: This paper explores the relationship between corporate social responsibility, corporate innovation, and corporate performance in developing countries. Firm level governance and corporate social responsibility data for 150 companies from 12 developing countries were collected from Datastream and Bloomberg for 2014–2019. The results show that in the context of developing countries there is no significant relationship between corporate social responsibility and corporate innovation. Our findings raise concerns about the level of R&D investments and commitment to corporate social responsibilities in developing economies.